Interpretation and Application of Criminal Law Regarding Blasphemy Under Article 156a of the Criminal Code - Nainggolan, Pandi Frenecius; Ikhsan , Rd Muhammad; Albariansyah, Hamonangan; Sinaga, Jimmy Christiansen (Faculty of Law, Universitas Lampung, 2024)
The offense of blasphemy is complex and confusing due to its three distinct definitions: offense according to religion, offense against religion, and offense related to religion. This lack of clarity results in no clear boundaries for defining what constitutes blasphemy. This article explores the legal interpretation of blasphemy through an analysis of various court decisions and the opinions of religious leaders. Utilizing normative research methods complemented by field data from interviews with religious leaders, the study reveals that Article 156a of the Criminal Code lacks a precise definition of blasphemy, leading to broad and varied interpretations. The subjectivity of determining blasphemy is evident, as it often depends on the identity of the offended party. Additionally, resolving blasphemy cases, such as those involving deviant sects, necessitates theological dialogue rather than immediate recourse to punitive measures. The article notes that judicial decisions in blasphemy cases frequently rely on the testimony of religious experts, sometimes without sufficient consideration of the expert’s qualifications or the quality of their explanation of blasphemy.